La equinoterapia y su influencia en los niños y niñas con trastornos del espectro autista en la fundación “San Miguel” cantón Salcedo provincia de Cotopaxi en el período 2014- 2015 - Chacón Espín, Sandra Lucia (2015)
The primary purpose of the study of equininotherapy is to know the main benefits is that and offers this therapy and contribute to the acquisition, and the improvement of and abilities and skills each children with autism spectrum, through some exercises using horses wich are an irreplaceable tool because it is a living being and it has the ability to transmit body heat and 110 vibrations per minute, three-dimensional movements, the same that are attracted by nerve structures and sent to the brain of the patient in the form of electrical waves making stimulation of the four main areas, allowing hat young children with this difficult disease, have the opportunity to be independent people and avoid relying on relatives in time for activities of daily living such as personal care and hygiene, assistance permanent therapy sessions reach their correct deficiencies in both physical and mental body.In conclusion equine therapy improves dysfunction capabilities in order to allowtle small integral development in the motor, cognitive, affective, social areas, and language, to interfere in the activities of society as a subject who thinks and feels. In addition to controlling their behavioral aspects that sometimes these people become too aggressive or extremely shy or vice versa, horse therapy can provide emotional, physical, stability who suffers from this difficulty giving he personal wellness.